The first record of Salsola paulsenii (Chenopodiaceae) in Ukraine, with taxonomic and nomenclatural comments on related taxa - Mosyakin, S.L. (Український ботанічний журнал, 2017)
Salsola paulsenii (Chenopodiaceae) is reported for Kyiv: several plants were found (September 2017) in
a sandy ruderal area of the northwestern part of Obolon, along railway tracks leading to the grain elevator and
brewery facilities of the Obolon Joint-Stock Co. Some co-occurring plants may represent hybrids of S. paulsenii and
S. tragus. Data on morphology and distribution of S. paulsenii and related species are provided. If established, this
species may become an invasive weed in Ukraine. Recent changes in taxonomy and nomenclature of Salsola sensu
lato are discussed. Nomenclatural information is provided for species of the Ukrainian flora formerly reported in
Salsola sensu lato and now placed in Salsola sensu stricto (incl. Kali), Soda, Caroxylon, Climacoptera, and Pyankovia. Адвентивний вид Salsola paulsenii (Chenopodiaceae) наведений для території м. Києва: декілька рослин були знайдені у вересні 2017 р. на піщаному ґрунті на рудеральній ділянці у північно-західній частині Оболоні, вздовж залізничних колій неподалік зернового елеватора та виробничих об'єктів ПрАТ "Оболонь". Наведені відомості про морфологічні особливості та поширення S. paulsenii та деяких споріднених видів. Якщо цей вид закріпиться в Україні, то він може стати інвазійним бур'яном. Розглянуті недавні зміни у систематиці та номенклатурі представників роду Salsola sensu lato. Надана номенклатурна інформація щодо видів флори України, які раніше наводилися у складі Salsola sensu lato, а тепер вміщені до родів Salsola sensu stricto (incl. Kali), Soda, Caroxylon, Climacoptera та Pyankovia. Адвентивный вид Salsola paulsenii (Chenopodiaceae) приведен для территории г. Киева: несколько растений были обнаружены в сентябре 2017 г. на песчаной почве на рудеральном участке в северо-западной части Оболони, вдоль железнодорожных путей поблизости зернового элеватора и производственных объектов ЧАО "Оболонь". Приведены сведения о морфологических особенностях и распространении S. paulsenii и некоторых родственных видов. Если этот вид закрепится в Украине, то он может стать инвазивным сорняком. Рассмотрены недавние изменения в систематике и номенклатуре представителей рода Salsola sensu lato. Предоставлена номенклатурная информация о видах флоры Украины, которые ранее приводились в составе Salsola sensu lato, а теперь перемещены в роды Salsola sensu stricto (incl. Kali), Soda, Caroxylon, Climacoptera и Pyankovia.